PHYTOCHEMICAL STUDIES ON DESMOSTACHYA BIPINNATA ROOTSTOCK - SHAKILA R,; ARUL ANTONY S,; GOPAKUMAR K, (International Journal of Pharma and Bio Sciences, 2015)
The ethanolic extract of rootstock of Desmostachya bipinnata (Family: Poaceae) was subjected to column chromatography over silica gel and eluted with different solvents of increasing polarity. 5-Hydroxymethyl 2-furfural along with β-amyrin, β-sitosterol, β-sitosterol glucoside, stigmasterol glucoside and sucrose were isolated and reported for the first time from the plant. Their structures were elucidated by physical and spectroscopic data.